2019
DOI: 10.1002/acn3.50816
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal prosodic correlation in frontotemporal dementia

Abstract: Communication accommodation describes how individuals adjust their communicative style to that of their conversational partner. We predicted that interpersonal prosodic correlation related to pitch and timing would be decreased in behavioral variant frontotemporal dementia (bvFTD). We predicted that the interpersonal correlation in a timing measure and a pitch measure would be increased in right temporal FTD (rtFTD) due to sparing of the neural substrate for speech timing and pitch modulation but loss of socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…However, the Greek patient populations with mxPPA, lvPPA, and svPPA had no significant reduction in speech rate (Karpathiou & Kambanaros, 2022; Potagas et al, 2022). Some English patient populations with lvPPA, svPPA, and bvFTD also had no significant differences in speech rate (Ash et al, 2013; Bird et al, 2000; Mack et al, 2015; Marcotte et al, 2017; Pressman et al, 2019; Rohrer & Warren, 2010; Sajjadi et al, 2012; Thompson, 2012; Wilson et al, 2010). Aside from Greek, all other non-English languages (Spanish, Italian, Hindi, and Czech) studying the FTD spectrum had a significant reduction in speech rate (Catricala et al, 2019; Daoudi et al, 2022; Matias-Guiu et al, 2022; Sachin et al, 2008; Silveri et al, 2012).…”
Section: Resultsmentioning
confidence: 94%
“…However, the Greek patient populations with mxPPA, lvPPA, and svPPA had no significant reduction in speech rate (Karpathiou & Kambanaros, 2022; Potagas et al, 2022). Some English patient populations with lvPPA, svPPA, and bvFTD also had no significant differences in speech rate (Ash et al, 2013; Bird et al, 2000; Mack et al, 2015; Marcotte et al, 2017; Pressman et al, 2019; Rohrer & Warren, 2010; Sajjadi et al, 2012; Thompson, 2012; Wilson et al, 2010). Aside from Greek, all other non-English languages (Spanish, Italian, Hindi, and Czech) studying the FTD spectrum had a significant reduction in speech rate (Catricala et al, 2019; Daoudi et al, 2022; Matias-Guiu et al, 2022; Sachin et al, 2008; Silveri et al, 2012).…”
Section: Resultsmentioning
confidence: 94%
“…These conflicting results might be due to the use of a different task (conversational speech) and measure (coefficient of variation of f0) of prosody and a smaller sample size of patients with sbvFTD than in this study. 38 Clinically differentiating patients with sbvFTD and svPPA can remain challenging, 39 especially at the individual level, and only a few clinical markers have been previously reported as discriminant in group-level analyses, specifically naming, repetition, and word comprehension (worse in svPPA) and empathy, emotion reading, difficulty identifying known people, and visuospatial abilities (worse in sbvFTD). 40 Expressive prosody may therefore represent an additional tool in clinical settings to better differentiate these 2 syndromes: a combination of several clinical markers might be optimal in differentiating patients with sbvFTD at the individual level in clinical practice, not only with patients with svPPA but also with patients with bvFTD.…”
Section: Discussionmentioning
confidence: 99%
“…Fewer studies have assessed prosody during speech production in bvFTD. These studies showed reduced stress (Vogel et al, 2017), mixed results for pitch modulation (altered in Nevler et al, 2017but preserved in Pressman et al, 2019and Vogel et al, 2017, and preserved intensity (Pressman et al, 2019).…”
Section: Prosodymentioning
confidence: 92%
“…Despite partly contradictory evidence (Vogel et al, 2017), speech rate seems globally preserved in bvFTD (Ash et al, 2013;Gunawardena et al, 2010;Pressman et al, 2019;Wilson et al, 2010). Indeed, even in the infrequent reports showing decreased speech rate, this deficit disappears upon excluding long pauses (Ash et al, 2016).…”
Section: Motor Speech Through Connected Speechmentioning
confidence: 99%